“The Greatest Man-Catcher of All”: The First Female Mounties, the Media, and the Royal Canadian Mounted Police - Schmidt, Bonnie (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2011)
The arrival of the first female Royal Canadian Mounted Police (RCMP) officers disrupted the highly masculinized image of a police force that was closely connected to ideal Canadian manhood and the formation of the nation. The absence of women from the historical record allowed the figure of the manly and heroic male Mountie to continue its dominance in official, academic, and popular histories of the police force. Both the print and broadcast media were complicit in disseminating these representations. When the first female Mounties were hired in 1974, editorial cartoonists and journalists frequently portrayed them in highly gendered terms that reflected understandings of femininity in operation in broader Canadian society at the time. The RCMP also articulated the arrival of the first female RCMP officers in gendered terms, reinforcing beliefs about manliness and masculinity as essential attributes for police officers. In contrast to these depictions, the oral histories of female RCMP officers present an alternative perspective that challenged and contested these gendered assumptions, establishing female Mounties as equal participants in the policing activities, and the history, of the RCMP on their own terms.